Soil Mercury Pollution in Nature-Based Solutions Across Various Land Uses: A Review of Trends, Treatment Outcomes, and Future Directions - Miguel Enrico Robles; Yugyeong Oh; Md Tashdedul Haque; Minsu Jeon; Lee-Hyung Kim (Applied Sciences)
Mercury (Hg) contamination in soils poses significant environmental risks. In response, various nature-based solutions (NbSs) have been developed and studied in the past to treat mercury along with other heavy metals from both point and nonpoint sources. However, various land uses present uncertainties in mercury mobility and treatment efficiency, affecting the scalability of NbS systems. In this study, a systematic review of peer-reviewed articles addressing mercury pollution in NbS soils was conducted. Results revealed that lakeside environments and mining areas are key Hg accumulation zones due to hydrological connectivity and anthropogenic pressures. Constructed wetlands were the most studied NbSs, where those with Acorus calamus and Aquarius palifolius as the main vegetation achieved >90% Hg removal efficiencies. Although NbSs achieved high Hg removal, anaerobic conditions were found to promote MeHg formation, a critical drawback. Moreover, biochar demonstrated potential for immobilizing Hg and reducing bioavailability, though certain types increased MeHg formation under specific redox conditions. Overall, the study highlighted the need for site-specific design, long-term field evaluation, and multidisciplinary strategies to optimize NbS performance for mercury removal. Furthermore, future research on the scalability of mercury-treating NbSs across diverse land uses is recommended to address mercury risks and improve effectiveness.